Disability Studies wobec natury postaw dyskryminujących - Wlazło, Marcin (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
With the development of disability studies the awareness of “false universalization of disability” increased. It was realized that both theoretical and practical abuse is to treat disability as the main and even the only factor that binds the environment of people with disabilities. The configurations of the aspects of oppression and discriminatory attitudes have been in fact much more complex and elaborate than it was originally thought according to the promotion of the social model of disability. The article addresses the problem of multiplicity and simultaneous oppression, in which disability co-exists among other factors, considering gender, race or age of human as no less important factors of marginalization, violation of law and social exclusion.